Relative Wealth and Risk Taking: A Short Note on the Friedman-Savage Utility Function - Gregory, Nathaniel (Journal of Political Economy, 1980)
This paper advances a hypothesis about individual attitudes toward risk that offers some theoretical justification for the Friedman-Savage utility function. Nonlinearity in utility results from the proposition that a consumer might care, for some reason, about his own wealth in comparison to the wealth of others in the population. It is suggested that individuals in the upper tail of the wealth distribution will typically be risk averse while those in the lower tail are risk preferrers.